PENINGKATAN PEMAHAMAN KONSEP DAN MOTIVASI BELAJAR SISWA MELALUI SIMULASI PHYSIC EDUCATION TECHNOLOGY (PhET) - Khaerunnisak Khaerunnisak (Postgraduate, University of Mataram, 2018)
Simulation of Physic Education Technology (PhET) is a simulation that contains about learning physics, chemistry and biology. PhET can replace a real lab into a virtual lab for PhET simulations can provide a learning experience at the same time play. This study aims to determine the effect PhET simulations of improving understanding the concept of the material liquid pressure and to determine the effect PhET simulations to increase student motivation to learn the material pressure liquid. Subjects in this study were students VIIIA and VIIIB MTsS Insan Quranic, Aceh Besar, with the number of students are 30 children. The VIIIA Class is the reference class in this study and the VIIIB classis the subject of experimental class. This study used a quasi-experimental. The instrumen research used understanding test of concepts and questionnaires. The conseptual understanding is conducted by pretest and posttest, each of the testconsisting of 15 questions choice. The questionnaire to measure students motivationusing Likert scale.Keywords: PhET Simulation, Conseptual Understanding, Learning Motivation